2013
DOI: 10.31186/jspi.id.8.1.65-76
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Tepung Daun Katuk (Sauropus androgynus) Dalam Ransum Terhadap Kualitas Telur Itik Mojosari (Anas javanica)

Abstract: The experiment is carried out to evaluate the effect of different levels Katuk (Sauropus androgynus) meal supplementation on egg quality of Mojosari ducks. A total of 36 Mojosari ducks was assigned to completely randomized design. The experimental animals weredistributed into four treatments groups as follows: R0 (diet without katuk leaf meal), R1 (diet + 2.5% katuk leaf meal), R2 (diet + 5% katuk leaf meal), R3 (diet + 7.5% katuk leaf meal) with three replication (nine ducks each). The research was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Statistical results showed that feeding rations A, B and C had no significant effect on eggshell weight (P> 0,05). The range of eggshell weight produced is between 9.01 -9.46 g. This value is greater than the weight of eggshell in other studies which only ranged from 7.05-7.4 g [18]. Eggshell weight in the Maju Jaya Livestock Group can be influenced by the calcium content in the feed and the size of the eggs produced [19].…”
Section: Eggshell Egg and Thicknessmentioning
confidence: 56%
See 1 more Smart Citation
“…Statistical results showed that feeding rations A, B and C had no significant effect on eggshell weight (P> 0,05). The range of eggshell weight produced is between 9.01 -9.46 g. This value is greater than the weight of eggshell in other studies which only ranged from 7.05-7.4 g [18]. Eggshell weight in the Maju Jaya Livestock Group can be influenced by the calcium content in the feed and the size of the eggs produced [19].…”
Section: Eggshell Egg and Thicknessmentioning
confidence: 56%
“…The eggshell thickness of feed C was in the range of eggshell thickness in other studies that ranged from 0.5 -0.6 [20]. The eggshell thickness that is in the range between 0.5 -0.52 is quite good in the transportation process because eggs are not easily broken [18].…”
Section: Eggshell Egg and Thicknessmentioning
confidence: 70%
“…Betakaroten merupakan merupakan provitamin A, yang penting untuk kesehatan. Kandungan karoten pada katuk dimanfaatkan untuk meningkatkan intensitas warna kuning pada telur itik (Simanjuntak et al, 2013). Kandungan klorofil yang tinggi bermanfaat sebagai pewarna makanan, antara lain pada produk tapai ketan dari Kabupaten Kuningan, Jawa Barat (Juhaeti et al, 2014).…”
Section: Hasil Dan Pembahasanunclassified
“…Pakan alami yang mengandung karotenoid diduga berasal dari rerumputan sawah dan ganggang air. Simanjuntak et al (2013) menyatakan bahwa itik yang dipelihara secara semi intensif dapat memenuhi kebutuhannya sendiri serta banyak mendapatkan pakan tambahan. Tumanggor et al (2017) menyatakan bahwa di sawah banyak terdapat pakan sumber karotenoid seperti hijauan, sehingga warna kuning telur itik yang dipelihara semi intensif lebih tinggi dibandingkan dengan itik yang dipelihara intensif.…”
Section: Skor Warna Kuning Telurunclassified
“…Pakan alami yang mengandung protein diduga berasal dari keong sawah. Hal ini sesuai dengan pendapat Simanjuntak et al (2013) yang menyatakan bahwa itik yang dipelihara semi intensif dapat memenuhi kebutuhannya sendiri serta banyak mendapatkan pakan tambahan. Rondonuwu et al (2018) menyatakan bahwa keong sawah adalah bahan pakan sumber protein yang harganya murah dan ketersediannya berlimpah.…”
Section: Indeks Putih Telurunclassified